2015
DOI: 10.1016/j.optom.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Monod kinetics model to determine in vivo human corneal oxygen-consumption rate during soft contact lens wear

Abstract: Present results are relevant for the calculation on the partial pressure of oxygen, available at different depths into the corneal tissue behind contact lenses of different oxygen transmissibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 15 publications
2
35
3
1
Order By: Relevance
“…This value represents the oxygen tension when corneal aerobic metabolism reaches its maximum oxygen consumption (that is, oxygen tension needed to achieve equilibrium in the cornea), and the aerobic metabolism reactions of glucose with oxygen (Krebs cycle) is saturated, bringing the system into an oxygen consumption independent of partial pressure. As observed, this model reproduces individual experiments for each lens (Balafilcon and Polymacon lenses), but it could not yield a good solution for both lenses simultaneously, even for two lenses of the same material but with different thicknesses, because the oxygen consumption rate is not the same in all cases.…”
Section: Theoretical Developmentmentioning
confidence: 83%
See 2 more Smart Citations
“…This value represents the oxygen tension when corneal aerobic metabolism reaches its maximum oxygen consumption (that is, oxygen tension needed to achieve equilibrium in the cornea), and the aerobic metabolism reactions of glucose with oxygen (Krebs cycle) is saturated, bringing the system into an oxygen consumption independent of partial pressure. As observed, this model reproduces individual experiments for each lens (Balafilcon and Polymacon lenses), but it could not yield a good solution for both lenses simultaneously, even for two lenses of the same material but with different thicknesses, because the oxygen consumption rate is not the same in all cases.…”
Section: Theoretical Developmentmentioning
confidence: 83%
“…Considering a one‐dimensional model for the cornea (or for any homogeneous slab of oxygen‐consuming tissue), oxygen tension as a function of time and position is given by the equation 2pcx2(QDk)c=1Dcpct where p c ( x , t ) is the oxygen partial pressure or tension in the cornea (mmHg), D c is the diffusion coefficient of oxygen in the corneal tissue (cm 2 /sec), k is the oxygen solubility coefficient in the corneal tissue, that is, Henry's law constant (cm 3 of O 2 /cm 3 of tissue/mm of Hg), x is the distance perpendicular to the surface (cm), Q c is the corneal oxygen consumption rate (ml of O 2 /cm 3 of tissue layer/sec), and t is time (s). Subscript c refers to quantities measured at the cornea.…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data have also demonstrated that lateral diffusion is minimal. Considering the cornea as a one‐dimensional homogenous tissue, the non‐steady‐state equation for the oxygen pressure as a function of time and position is given by the equation Dc2pcx2Q()pnormalcknormalc=pct where p c ( x , t ) is the oxygen tension in the cornea (in mmHg), D c is the oxygen diffusion coefficient into the cornea, k c is the oxygen solubility coefficient in the corneal tissue (cm 3 of O 2 /cm 3 of tissue/mmHg), x is the distance perpendicular to the surface (in cm), Q ( p c ) is the oxygen consumption rate (mL of O 2 /cm 3 of tissue layer/s), and t is time (in s). The subscript c refers to the quantities measured at the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various researchers have presented a Monod model of time‐dependent oxygen diffusion in the cornea . Michaelis–Menten‐type relationship for oxygen uptake kinetics was used to complete this model . The experimental data of Bonanno et al were used to validate the model and to determine the oxygen consumption and diffusivity of the cornea by fitting the model to different cases of CL transmissibility.…”
Section: Introductionmentioning
confidence: 99%